Ketidakefektifan Malacca Strait Patrol dalam Mengatasi Pembajakan dan Perompakan di Selat Malaka dan Singapura - Muhammad Rizky Pangestu; Mohamad Rosyidin (Journal of International Relations Diponegoro, 2019)
This research aims to find out the reason why the join patrol in the Malacca Strait and Singapore, the Malacca Straits Patrol (MSP) ineffective to maintain security in the Malacca Strait and Singapore. The ineffective can be seen in the 2014 ReCAAP data where in 2014 there were 44 cases of piracy in the Malacca Strait and Singapore. Up 32 cases from 2013 and in 2015 it rose again to 94 cases. In analyzing the case this research will use realist theory. In the realist theory it is stated that in achieving a goal a country needs its national power. But the national power must be transformed into the real power of the country's government. Then for the data this study uses a literature study. Whereas for data analysis this research uses congruent data analysis. The results of this study indicate that the ineffective of the MSP in tackling cases of piracy and piracy is caused by thelimited military power of MSP members to carry out anti-piracy operations. This condition made worse by the quality of government of Malacca Strait Patrol member countries which are not good because they are not so concerned about these limitations.